2002
DOI: 10.1097/00000539-200204000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal Lidocaine Prevents Cardiovascular Collapse and Neurogenic Pulmonary Edema in a Rat Model of Acute Intracranial Hypertension

Abstract: In a rat model of intracranial balloon inflation, intrathecal lidocaine prevented cardiovascular collapse and neurogenic pulmonary edema. Descending neural pathways are involved in the development of cardiopulmonary complications associated with acute intracranial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…The hemodynamic response to brain-stem injury and the NPO can be prevented by ␣-adrenergic blockade, spinal cord transection, splanchnectomy, and spinal anesthesia, but not by adrenalectomy or ␤-blockade (62)(63)(64)(65)(66). These observations indicate that norepinephrine released by the nerve endings of the sympathetic nervous system is the mediator and not adrenal epinephrine.…”
Section: Avlonitis Et Almentioning
confidence: 85%
“…The hemodynamic response to brain-stem injury and the NPO can be prevented by ␣-adrenergic blockade, spinal cord transection, splanchnectomy, and spinal anesthesia, but not by adrenalectomy or ␤-blockade (62)(63)(64)(65)(66). These observations indicate that norepinephrine released by the nerve endings of the sympathetic nervous system is the mediator and not adrenal epinephrine.…”
Section: Avlonitis Et Almentioning
confidence: 85%
“…A randomized, controlled clinical trial has demonstrated that the addition of thoracic epidural to conventional general anesthesia in patients undergoing off‐pump coronary artery bypass graft surgery, accounts for a significant reduction in the incidence of postoperative arrhythmias and improvement in overall quality of recovery [15]. LID prevents cardiovascular collapse in a rat model of acute intracranial hypertension [16]. It was reported that thoracic epidural anesthesia could reduce myocardial infarcted size after coronary artery occlusion in dogs [17].…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic hyperactivity during sudden intracranial hypertension leads to cardiovascular instability, myocardial dysfunction and neurogenic pulmonary edema. One study o b s e rved that intrathecal lidocaine prevents cardiovascular collapse and neurogenic pulmonary edema in a rat model of acute intracranial hypertension 22 .…”
Section: Discussionmentioning
confidence: 99%